Funding virtue : civil society aid and democracy promotion - Ottaway, Marina; Carothers, Thomas, 1956- (Carnegie Endowment for International Peace, 2000)
In recent years the United States and many other international donors have embraced civil society aid as a key tool of democracy promotion. They support thousands of NGOs around the world in the name of civil society development, investing in these organizations high hopes for fostering democratic participation and values. Funding Virtue: Civil Society Aid and Democracy Promotion critically examines this burgeoning field. A diverse, distinguished collection of democracy experts and civil society practitioners from both donor and recipient countries analyze civil society aid in five regions, including country case studies of South Africa, the Philippines, Peru, Egypt, and Romania. The authors focus on crucial issues and dilemmas, such as the relationship between donor conceptions of civil society and local realities, the effects of civil society programs, and how aid can be improved. The book's broad geographic reach, practical focus, and analytic rigor make it an invaluable guide to this vital new area of international affairs.